PENGARUH PENERAPAN IFRS DALAM PENGUNGKAPAN INTELLECTUAL CAPITAL PADA PERUSAHAAN BERTEKNOLOGI TINGGI: Saat Konvergensi IFRS dan Penerapan Full Adopsi IFRS - Rahmadhani, Sari; Nur, Arkanuddin (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2016)
The purpose of this research was to examine the impact ofInternational Financial Reporting Standards (IFRS) on the disclosure ofIntellectual Capital. This study also examines the different of IntelectualCapital disclosure by using the index of intellectual capital disclosurewhich presented in the financial statements of high-tech manufacturingfirms. With the period of time research is at the time of IFRS convergenceand at the time of full application of IFRS. Using 96 companies listed onthe Indonesia Stock Exchange in 2008 and 2012. The study wasconducted using multiple regression analysis techniques. The resultsshowed that the adoption of IFRS could improve the practice of corporateintellectual capital disclosure. The result of t-test sample,showedstatistically intellectual capital disclosure after full adoption ofIFRS is higher than intellectual capital disclosure before full adoption ofIFRS.